2022
DOI: 10.3389/fphar.2022.1010103
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate juice fermented by tannin acyl hydrolase and Lactobacillus vespulae DCY75 enhance estrogen receptor expression and anti-inflammatory effect

Abstract: Phenolics are phytochemicals in plants, fruits, and vegetables have potential health-promoting efficacies. However, mostly available as a complex form. So, to increase the contents and nutritional value of the phenolic compounds, fermentation is most readily used in the food industry. Especially, the hydrolyzable tannins present in the pomegranate that can be liberated into monomolecular substances, which enhances biological activity. Thus, this study aims to convert hydrolyzable tannins to ellagic acid by fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…In matured cells lipid droplets were visualized using oil red O to confirm adipogenesis in 3T3-L1 cells following a previously described method ( 23 ). Briefly, differentiated cells were washed with 1× phosphate-buffered saline (PBS) and fixed using 4% formalin for 2 h. Cells were then dried and soaked in 60% isopropanol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In matured cells lipid droplets were visualized using oil red O to confirm adipogenesis in 3T3-L1 cells following a previously described method ( 23 ). Briefly, differentiated cells were washed with 1× phosphate-buffered saline (PBS) and fixed using 4% formalin for 2 h. Cells were then dried and soaked in 60% isopropanol.…”
Section: Methodsmentioning
confidence: 99%
“…Reducing potential was evaluated according to Akter et al ( 23 ). The reaction mixture containing 100 μL samples, 250 μL phosphate buffer, and 250 μL of 1% potassium ferricyanide was incubated at 50°C on a heat block for 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…The mineralization of the extracellular matrix is a critical process in bone formation, closely linked to the development and differentiation of osteoblasts [21]. In order to assess the impact of extracts from steamed SHF on osteoblast development, we conducted ARS staining to measure calcium accumulation within the extracellular matrix.…”
Section: Effect Of Steaming Of Shf On Mineralization and Calcium Depo...mentioning
confidence: 99%
“…Adiposity in the bone marrow is linked to secondary causes of OP, such as diabetes mellitus, obesity, and use of glucocorticoids [ 6 ]. OP can arise from irregular bone homeostasis, which is linked to obesity and chronic inflammation [ 7 ]. Recent studies have revealed that those who are obese have higher incidences of OP and bone fractures than those who are not obese [ 8 ].…”
Section: Introductionmentioning
confidence: 99%